Bivalve-specific gene expansion in the pearl oyster genome: implications of adaptation to a sessile lifestyle. Issue 1 (December 2016) - Takeuchi, Takeshi; Koyanagi, Ryo; Gyoja, Fuki; Kanda, Miyuki; Hisata, Kanako; Fujie, Manabu; Goto, Hiroki; Yamasaki, Shinichi; Nagai, Kiyohito; Morino, Yoshiaki; Miyamoto, Hiroshi; Endo, Kazuyoshi; et al.
Abstract Introduction Bivalve molluscs have flourished in marine environments, and many species constitute important aquatic resources. Recently, whole genome sequences from two bivalves, the pearl oyster, Pinctada fucata, and the Pacific oyster, Crassostrea gigas, have been decoded, making it possible to compare genomic sequences among molluscs, and to explore general and lineage-specific genetic features and trends in bivalves. In order to improve the quality of sequence data for these purposes, we have updated the entireP. fucata genome assembly. Results We present a new genome assembly of the pearl oyster, Pinctada fucata (version 2.0). To update the assembly, we conducted additional sequencing, obtaining accumulated sequence data amounting to 193× theP. fucata genome. Sequence redundancy in contigs that was caused by heterozygosity was removedin silico, which significantly improved subsequent scaffolding. Gene model version 2.0 was generated with the aid of manual gene annotations supplied by theP. fucata research community. Comparison of mollusc and other bilaterian genomes shows that gene arrangements of Hox, ParaHox, and Wnt clusters in theP. fucata genome are similar to those of other molluscs. Like the Pacific oyster, P. fucata possesses many genes involved in environmental responses and in immune defense. Phylogenetic analyses of heat shock protein70 and C1q domain-containing protein families indicate that extensive expansion of genes occurred independently in each lineage. Several gene duplication events prior to the split between the pearl oyster and the Pacific oyster are also evident. In addition, a number of tandem duplications of genes that encode shell matrix proteins are also well characterized in theP. fucata genome. Conclusions Both thePinctada andCrassostrea lineages have expanded specific gene families in a lineage-specific manner. Frequent duplication of genes responsible for shell formation in theP. fucata genome explains the diversity of mollusc shell structures. These duplications reveal dynamic genome evolution to forge the complex physiology that enables bivalves to employ a sessile lifestyle in the intertidal zone.